Tafsir Realis terhadap Makna dan Simbol Alquran bagi Masyarakat Kabupaten Probolinggo - Mun'im, A Rafiq Zainul (Madania: Jurnal Kajian Keislaman, 2017)
Realist Interpretation and Symbolic Meaning of the Quran for the Society of Probolinggo Regency. All Moslem scholars believe that people have own ways to respond, interact, and function Quranic verses within their lives. Their effort is only to maintain the majesty of the Quran. Therefore, this study will examine how does the symbolization of Quranic verses has functions for, how do they elucidate and interpret, how do their interpretation and symbolization of Quranic verses take a position in Quranic discourse, especially in Probolinggo. The qualitative paradigm was chosen to clarify those questions. Meanwhile, the approach to data is Turner’s processional approach of symbolism and Levi Strauss’ structuralism. Through this discussion, the result of research concluded that the symbolization of Quranic verses has four functions, mainly (1) source of religious teaching; key element of ritual and ceremonial activities; ornament of calligraphy; and mystical medium, (2) symbolization of verses indicates Probolinggo people’s stance in using Quran; the meaning of symbolized verses is possible to trace from their consciousness and unconsciousness, and (3) interpretation and symbolization of Quranic verses take a position in the light of realist interpretation and meaningful interpretation as well as the living Quran, which have implied not only theoretical study of Quranic verses, but also practical function for society in the real life.